Political Party Leaders’ Branding: The Case of the UK Conservative & Labour Parties - Akkawi, Dania (AUC Knowledge Fountain, 2026)
Political party branding has become increasingly shaped by digital communication, particularly through social media platforms where voters actively engage with political leaders and one another. This thesis studies “Political Party Branding: The Case of the UK Conservative & Labour Parties”, focusing specifically on the interconnections between Stakeholder Theory and Emotional Branding Theory on voter opinion and voter interest, during the 2024 UK general election. Through a comparative analysis of Rishi Sunak (Conservative Party) and Keir Starmer (Labour Party), the study tests theoretical propositions drawn from the theories to assess how visibility and emotional intensity shape voter opinion and interest. Using a quantitative content analysis of 2,000 posts over eight months (1,000 from each political party leader), the study integrates social media metrics, including post views, engagement rates, and sentiment scores, to evaluate behavioral and affective responses, focusing on social media activity via commenters. The results show that visibility of commenters drives engagement but does not impact sentiment, meaning that reaching more people increases interaction but does not necessarily improve perception. Moreover, emotional intensity appears to generate more negative reactions without boosting engagement, and the comparison between leaders also shows that challengers convert visibility into engagement more effectively but are faced with greater scrutiny over authenticity, while incumbents experience weaker engagement and less backlash. Overall, the study shows that potential refinement to both theories to accommodate political branding may be in order. While the study shows the importance of large-scale social media analysis and impact of commenters in the context of brand consistency, authenticity and emotional intensity, the research suggests that future research should expand cross-national comparisons, employ experimental designs to establish causality, and examine how emotional authenticity and platform-specific dynamics further shape political brand performance in the ever-evolving digital landscape.